Nurses’ Knowledge and Attitude towards Postoperative Pain Management in Ghana - Shamsu-Deen Mahama Adams; Shokoh Varaei; Fatemeh Jalalinia (Pain Research and Management)
Background. Pain management is a very important aspect of nursing care among postoperative patients. Deficit in the knowledge and bad attitude towards pain management among nurses remain a problem in Ghana. In order to manage pain better in the surgical wards, nurses should be well equipped with knowledge of pain assessment and management. Purpose. The purpose of the study was to determine nurse’s knowledge and attitude towards pain management among postoperative patients in surgical units in Ghana. Methodology. This study used the quantitative study approach with a descriptive cross-sectional study design. A sample of 211 nurses was recruited using the convenience sampling method. Data were collected using a questionnaire regarding postoperative pain management. Descriptive statistics, Pearson’s correlation coefficient, and the chi-squared test were used to analyze the data using SPSS version 16.0. Results. The mean age of the nurses was 29.77, with the youngest nurse being 23 years and oldest being 39 years. Majority (72.5%) of nurses had moderate knowledge, and 89.6% of the nurses had negative attitude towards pain management. There was no significant relationship between nurse’s knowledge and years of experience as a nurse (r = −0.03, p=0.64), as well as no significant relationship between knowledge and number of years working in the surgical ward (r = 0.06, p=0.36). Also, there was no significant relationship between nurses’ knowledge and nurses’ attitude (r = 0.06, p=0.36). Conclusion and recommendation. The level of knowledge and attitude towards postoperative management were generally inadequate among nurses. Therefore, there is the need to implement in-service training on pain management for nurses working in the surgical units frequently.